2020
DOI: 10.3390/life10050057
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the C-Terminal Domain Small Phosphatase 1

Abstract: The human C-terminal domain small phosphatase 1 (CTDSP1/SCP1) is a protein phosphatase with a conserved catalytic site of DXDXT/V. CTDSP1’s major activity has been identified as dephosphorylation of the 5th Ser residue of the tandem heptad repeat of the RNA polymerase II C-terminal domain (RNAP II CTD). It is also implicated in various pivotal biological activities, such as acting as a driving factor in repressor element 1 (RE-1)-silencing transcription factor (REST) complex, which silences the neuronal genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 154 publications
0
13
0
Order By: Relevance
“…We found that hsa-let-7b_5c acquired 292 additional targets, including VBP1 and CTDSP1. Recently, some studies demonstrated that CTDSP1 inhibited the proliferation, migration and invasion of cancer cells by inhibiting the dephosphorylation of TWIST and AKT, suggesting a tumor suppressor role of CTDSP1 ( Rallabandi et al, 2020 ; Yang X. et al, 2021 ). Furthermore, a study showed the role of CTDSP1 in cell cycle arrest during the G1/S transition through c-Myc-mediated dephosphorylation of retinoblastoma protein (RB) ( Liu et al, 2016 ; Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that hsa-let-7b_5c acquired 292 additional targets, including VBP1 and CTDSP1. Recently, some studies demonstrated that CTDSP1 inhibited the proliferation, migration and invasion of cancer cells by inhibiting the dephosphorylation of TWIST and AKT, suggesting a tumor suppressor role of CTDSP1 ( Rallabandi et al, 2020 ; Yang X. et al, 2021 ). Furthermore, a study showed the role of CTDSP1 in cell cycle arrest during the G1/S transition through c-Myc-mediated dephosphorylation of retinoblastoma protein (RB) ( Liu et al, 2016 ; Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The HAD family of phosphatases or hydrolases have a wide spectrum of substrates that includes proteins, lipids, small molecules, and metabolites [77] (Table 2). Multiple sequence alignment and phylogenetic analysis revealed that trypanosomatid-Tim50 is grouped with Tim50s from other eukaryotes and is distinctly separated from other HAD-family proteins like lipin [75], small CTD-phosphatases (SCP1, FCP1) [78], ubiquitin-like domain containing CTD phosphatase (UBLCP) [79], and Dullard phosphatase [80] (Figure 3). Therefore, it seems TbTim50 is a special kind of HAD phosphatase with both protein-and lipid phosphatase activities and in addition plays role in protein translocation.…”
Section: Tim50 Primary Structure and Membrane Topologymentioning
confidence: 99%
“…Our results show a small, non-statistically significant difference between REST and CTDSP1 knockdown in promoting the expression of BDNF and NGF. This difference may be due to the activity of structural and functional paralogs of CTDSP1, namely CTDSP2 and CTDSPL, which are not affected by CTDSP1 siRNA 33,35,36 .…”
Section: Discussionmentioning
confidence: 99%